2004
DOI: 10.1093/molehr/gah146
|View full text |Cite
|
Sign up to set email alerts
|

HCG up-regulates survivin mRNA in human granulosa cells

Abstract: The apoptosis of granulosa cells is involved in follicular atresia and degeneration of the corpus luteum. The mechanisms that regulate follicular atresia and luteal degeneration remain obscure. Survivin is a member of the family of inhibitors of apoptosis protein that is expressed during fetal development and in cancer tissues. The present study investigates the expression of survivin, as well as its regulation and function in granulosa cells. We identified survivin at the protein level in granulosa cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Survivin expression has also been reported in melanocytes (82), keratinocytes (83), testes (84), and ovary (85) in humans. Stem cell factor and human chorionic gonadotropin also induce survivin expression in testes (84) and in ovarian granulosa cells (85), suggesting that survivin may have a role in the regulation of spermatogenesis and oogenesis.…”
Section: Survivin In Other Adult Tissuesmentioning
confidence: 99%
“…Survivin expression has also been reported in melanocytes (82), keratinocytes (83), testes (84), and ovary (85) in humans. Stem cell factor and human chorionic gonadotropin also induce survivin expression in testes (84) and in ovarian granulosa cells (85), suggesting that survivin may have a role in the regulation of spermatogenesis and oogenesis.…”
Section: Survivin In Other Adult Tissuesmentioning
confidence: 99%
“…In fact, HCG increases Bcl-2 expression and decreases Bax expression in the corpus luteum in vitro [49,65]. In addition, there is a report indicating that HCG upregulates survivin in human granulosa cells, which is an inhibitor of apoptosis protein that directly interacts with several caspases to inhibit apoptosis [64].…”
Section: Anti-apoptotic Effects Of Hcgmentioning
confidence: 99%
“…Extracellular adenosine triphosphate (ATP) induces apoptosis via mitochondrial depolarization in human granulosa cells in vitro, and HCG inhibits ATP-induced apoptosis [63]. Matsubara et al [60] also reported that suppression of apoptosis by HCG is mediated not only by inhibition of the Fas pathway but also by the Bcl-2 and Bax system in luteinized granulosa cells [64]. In fact, HCG increases Bcl-2 expression and decreases Bax expression in the corpus luteum in vitro [49,65].…”
Section: Anti-apoptotic Effects Of Hcgmentioning
confidence: 99%
“…Such DcRs lack an intracellular DD and are proposed to sequester and prevent TRAIL binding to DR4 or DR5 and/or interfere with receptor trimerization (Degli-Esposti et al 1997a, 1997b, Emery et al 1998. In mammalian granulosa cells, the expression of a variety of intracellular proteins, such as Fas-associated death domain-like interleukin-1b-converting enzyme (FLICE)-inhibiting protein (FLIP L ; Xiao et al 2002), anti-apoptotic Bcl-2 family members (e.g., Bcl-2 and Bcl-x; Tilly et al 1995, Hsu et al 1996, inhibitor of apoptosis proteins (IAPs; Xiao et al 2001), and survivin (Kumazawa et al 2005), can attenuate caspase activity and/or are associated with a reduced incidence of apoptosis.…”
Section: Introductionmentioning
confidence: 99%